90 days to success marketing and advertising your small business - 520953 Hoxie, Mark (Boston : Course Technology)
"Empowers small business owners with a practical plan of action to achieve successful results from their advertising and marketing efforts; provides techniques that are applicable to any business owner, regardless of industry; examines and explains all formes of advertising (e-marketing, radio, newspaper, television, magazine, and more)"--Cover.